FAKTOR PEMBENTUKAN CITRA TERHADAP OPINI PUBLIK PADA KANTOR KELURAHAN JATIROKEH - Arina Muntazah (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2020)
This study aims to determine the effect of image-forming factors such as physical identity, non- physical identity, organizational management, product quality, activities and relationships. Variable X1 is physical identity, variable X2 is non-physical identity, variable X3 is organizational management, variable X4 is product quality, variable X5 is activities and relationships, and variable Y is public opinion. This research is a quantitative research with correlational descriptions. The sample used here is 100 people. The data was collected using a questionnaire and the results were calculated using a Likert scale. In addition, several tests were used to make the data valid. Namely the validity test, reliability test, and classic assumption test which includes the normality test and multicollinearity test. Furthermore, the data were analyzed using multiple linear regression analysis. From the results of data analysis and discussion, it is known that simultaneously the variables X1, X2, X3, X4, X5, and Y. The contribution of the five variables is 59.1%, the remaining 40.9% is influenced by other factors besides these. five variables. In this study, it is known that non-physical identity variables are the most dominant variables affecting public opinion. The existence of a good non-physical community identity perceives the success of the Jatirokeh Village Office. The influence of 59.1% can be assumed that the formation of a high image, this means that the image of the Jatirokeh Village Office can be said to be successful or accepted by the community.